Variation of match statistics and football teams` match performance in the group stage of the EUFA Champions league from 2010 to 2017 - Yi, Q.; Gómez, M.-A.; Liu, H.; Sampaio, J. (Kinesiology, 2019)
The aim of this study was to identify the relationships between the variation of match variables and teams` match performance. Data from all 768 matches played at the group stage of the UEFA Champions League from season 2009/1010 to 2016/2017 were analysed. The non-clinical magnitude-based inferences were used to identify the differences of technical variation between the teams. Autocorrelation function, correlation analysis and generalised linear model were used to examine the relationships between the variation of match variables and teams` match performance. Results showed that the qualified teams demonstrated a more stable match performance on the variables related to goal scoring, attacking and passing, while the non-qualified teams displayed a more stable match performance on the variables related to defending. The coefficients of variation (CV) of all the variables related to goal scoring and the variables related to attacking and passing showed negative relationships with the teams` match performance, while the CVs of the variables related to defending showed positive relationships with the teams` match performance. Findings of this study can provide useful information about the fluctuation of match variables, contributing to the development of specific training interventions to enhance teams` performance in key indicators.